ByzRev 06.2024.064: Zhenya Zhekova – Stela Doncheva, Production of Imitative Byzantine Folles in the First Bulgarian Kingdom.: Veliko Tarnovo: Faber 2022. - Curto Pelle, Ilia (The Byzantine Review, 2024)
Zhenya Zhekova – Stela Doncheva, Production of Imitative Byzantine Folles in the First Bulgarian Kingdom. Veliko Tarnovo: Faber 2022. 316 pp., color illustrations. – ISBN 978-619-00-1586-4